Nano antioxidant serum ethanol extract lime peel (Citrus aurantifolia S.) - Fortuna, Putri Asabella; Mugiyanto, Eko; Waznah, Urmatul; Rahmasari, Khusna Santika (Universitas Muhammadiyah Malang, 2022)
Serum is a cosmetic that has received great attention from the industry, but the main challenges are appearance, transparency and public acceptance of herbal active ingredients. On the other hand, herbal cosmetics, such as those using lime peel, are also growing. This study aims to determine the antioxidant activity of lime peel made in a nano extract serum preparation. The method for making nano extracts uses ionic gelation with PSA (Particle Size Analyzer) and Zeta Potential characterization. The concentration of nano serum of lime peel ethanol extract used was 0.5%; 1%; and 3%. Meanwhile, the antioxidant activity testing method uses DPPH and data analysis applied one-way ANOVA then by Tukey test. The results of the nano extract serum formulation using organoleptic testing are transparent, thick and liquid, odorless, and feel moist on the skin. The results of nanoparticle characterization using PSA measurements with three replications were 295.1; 320.3; 385.4 nm and the results of testing the zeta potential of nanoparticles with three replications, namely 3.2; 3.4; 6.0mV. Furthermore, the results of the antioxidant activity test on the basis of the preparation formula are classified as weak (IC50 value of 156.22 μg/mL); Meanwhile, preparation formula with a concentration of 0.5%; 1%; 3% are considered very strong (IC50 value of 46.39 μg/mL; 41.06 μg/mL; 36.27 μg/mL). The results of data analysis consider significance of p value below 0.05. The conclusion is nano lime peel extract meets the requirements and the serum preparation meets the requirements and has antioxidant activity.